Phytochemical and Antioxidant Characterization of Extracts from Unexplored Medicinal Plants Salix schwerinii and Salix kochiana - Jeongho Lee; Yunseok Song; Hyerim Son; Seunghee Kim; Kang Hyun Lee; Badamtsetseg Bazarragchaa; Changyoung Lee; Hah Young Yoo (Horticulturae, 2023)
For a long time, species of the genus Salix have been widely utilized and studied as medicinal plants; however, the biological activity and phytochemical composition of Salix schwerinii (SS) and S. kochiana (SK) have not been studied at all. This study investigated the antioxidant properties of SS and SK extracts and detected phytochemical compounds in the extracts. The results showed that the antioxidant activities (IC50) of SS extract, SK extract, and ascorbic acid (reference) were as follows, respectively: 169.8, 79.8, and 71.2 μg mL−1 for ABTS cation radical scavenging and 38.4, 26.2, and 9.3 μg mL−1 for DPPH free radical scavenging. The results imply that SK has a high potential as a natural antioxidant. The phytochemical compositions of extracts (mg g−1) were analyzed as follows: SS extracts, 217.7 phenolics (1.54 catechin, 0.86 syringic acid, 0.46 luteolin, and others) and 5.06 salicin; SK extracts, 71.0 phenolics (0.54 catechin, 0.28 myricetin, 0.12 salicylic acid, and others) and 2.11 salicin. Compared to previous studies, the present findings go further to highlight that SS deserves attention as a novel source of salicin. The present study highlights the need for further studies on the aspects of medicinal functions of the extracts, bioprocess design for efficient phytochemical extraction, and applications of bioactive substances.